The Terrestrial Vertebrate Fauna of Bago River, Negros Occidental, Philippines - Bacosa, Rogie; Averia , Leonardo T.; Bucol, Abner A.; Menes , Carmen C.; Linaugo, Joji D.; Dales, Alma D.; Bangoy, Shirley (Silliman Journal, 2022)
The terrestrial vertebrates of Bago River were surveyed for six NPOUITJOBOEVTJOHQVSQPTJWFTBNQMJOHUFDIOJRVFT There were 129 bird species, 19 reptiles, 10 amphibians, and 14 mammals (10 of which were bats) documented in the four sampling stations of the river. Conservation and management efforts for Bago River are urgently needed to ensure the sustainability of its biodiversity.